2015
DOI: 10.1016/j.jtherbio.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Survival of rapidly fluctuating natural low winter temperatures by High Arctic soil invertebrates

Abstract: The extreme polar environment creates challenges for the resident invertebrate communities and the stress tolerance of some of these animals has been examined over many years. However, although it is well appreciated that standard air temperature records often fail to describe accurately conditions experienced at microhabitat level, few studies have explicitly set out to link field conditions experienced by natural multispecies communities with the more detailed laboratory ecophysiological studies of a small n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 67 publications
1
28
0
Order By: Relevance
“…Thus, the snow removal resulted simply in a reduction in the periods with snow cover. It is probable that climate change will lead to a reduction in snow cover depth and duration (Christensen et al, 2013;Convey et al, 2015). Thus, snow cover will only protect overwintering animals periodically (as in this experiment), and strong frost, even when short lasting, may result in high mortality.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the snow removal resulted simply in a reduction in the periods with snow cover. It is probable that climate change will lead to a reduction in snow cover depth and duration (Christensen et al, 2013;Convey et al, 2015). Thus, snow cover will only protect overwintering animals periodically (as in this experiment), and strong frost, even when short lasting, may result in high mortality.…”
Section: Discussionmentioning
confidence: 89%
“…Warmer temperatures during winter could increase the chances of survival of overwintering invertebrates (e.g., Bale & Hayward, 2010;Bradshaw & Holzapfel, 2010;Templer et al, 2012, but see also e.g., Sorvari et al, 2011, Haatanen et al, 2015. However, climate change will probably not only affect temperature during winter, but is also likely to result in a reduction in the depth and duration of snow cover (Christensen et al, 2013;Convey …”
Section: Introductionmentioning
confidence: 99%
“…; Convey et al . ), though these results may be influenced by experimental conditions and the specific adaptations of the organisms being studied (Henry ). To further complicate matters, the sub‐lethal effects of long‐term exposure to FTCs are also generally poorly understood in soil communities (Knox et al .…”
Section: Introductionmentioning
confidence: 99%
“…Low temperatures and FTCs are of particular importance to small, poikilothermic animals such as nematodes, as they are highly susceptible to freeze damage (Bokhorst et al 2012) and have limited capacity to move to potential refugia. Previous field and laboratory studies have revealed differing effects of FTCs on populations of soil microinvertebrates (Bale et al 2001;Sulkava & Huhta 2003;Sjursen et al 2005;Convey et al 2015), though these results may be influenced by experimental conditions and the specific adaptations of the organisms being studied (Henry 2007). To further complicate matters, the sub-lethal effects of long-term exposure to FTCs are also generally poorly understood in soil communities (Knox et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Soil ecosystems in polar and alpine regions are exposed to a suite of freezing and desiccation stresses. While the ecosystem response to freeze-thaw frequency has been more thoroughly investigated in arctic and boreal regions (e.g., Bale et al, 2001;Bokhorst et al, 2012;Convey et al, 2015;Henry, 2007;Larsen et al, 2002;Schimel & Clein, 1996;Sjursen et al, 2005;Sulkava & Huhta, 2003), relatively little work has been done in Antarctic regions. During the austral summer (December to February), Antarctic active layer soils warm to temperatures above the freezing point of liquid water.…”
mentioning
confidence: 99%